Feasibility assessment of immunization carpool model for <2 years children in rural Pakistan. (20th October 2021) - Ali, RF; Iftikhar, S; Shah, MT; Ali Khan, A; Siddiqi, DA; Chandir, S
Abstract:  : Almost 20 million children globally do not get routine vaccines, 1.4 million of which reside in Pakistan. Immunization coverage in rural settings of Pakistan, comprising >60% population, is lower than their urban counterparts. Barriers such as distant-centers, lack of transportation, and restrictions on women to travel alone, exacerbate the problem. We introduced immunization carpool services in rural settings to facilitate vaccination of < 2 years children. Low-coverage immunization clinics were selected based on availability of vaccinators and vaccines in Shikarpur, a rural district in Pakistan. Local transport providers were identified and vehicles were rented-in. Community mobilization was done through awareness sessions and branding vehicles. Data was recorded on the number of round trips and immunization visits facilitated by each vehicle. Details of children transported and feedback on carpool services were captured from caregivers. Immunization coverage was calculated using the government's electronic immunization registry data. Between January to October 2020, 6 vehicles were deployed, which provided free transport services in 98 catchment areas of 4 immunization clinics. On average, each vehicle completed 420 (SD: 58.2) round trips and facilitated 781 (SD: 171) immunization visits. A total of 2, 391 children were enrolled, 1, 182 (49.7%) of them were females and 1, 197 (50%) aged <6months. Enrolled children compared to non-enrolled at the same immunization clinic, showed 19.1% higher coverage rate for penta-3 (81% vs 68%, p < 0.00) and 23.6% for measles-2 (73% vs 57%, p < 0.00). Immunization timeliness among enrolled children increased by 4.8% for penta-3 (9% vs 4%, p < 0.00) and 18% for measles-2 (25% vs 7%, p < 0.00). Reported advantages of services include time-saving (92%), cost-saving (79%), and reduced dependence on family members (95%). Immunization carpool service is well-accepted by rural women and can improve immunization coverage and equity in rural areas. Key messages: Provision of commuting options can overcome accessibility barriers and has the potential to improve immunization coverage and timeliness. Free transport services for rural women could aid in promoting gender equity and reducing urban-rural disparities.